Effects of different intensities of flexibility training on explosive force - dos Santos Galdino, L. A.; Nogueira, C. J.; Costa e Silva Galdino, E.; Perrout de Lima, J. R.; Gomes de Souza Vale, R.; Martin Dantas, E. H. (Human Movement, 2010)
To verify whether there are changes in the performance levels of the explosive force when the same muscle group previously underwent different intensities of flexibility training (stretch & flex). Basic procedures. The tests were performed with 25 females on three consecutive days and were preceded by a 10-minute warm-up period. First, each participant performed a maximum vertical jump on a contact platform. The jump was repeated after 10 minutes, and the first day was considered the control (C). On the second day, a routine of stretching exercises (S) was included, and on the third day, the same routine, but intensified with a maximum static stretching exercises (flexibilizing - F), was used. Main findings. The height reached in the control jump decreased by 0.17%, showing no influence on the performance when the jump happened on the same day, with a time-interval of only 10 minutes (p = 0.903). On the day of the stretching routine, there was a reduction of 3.6% (p = 0.001), and on the third day with flexibilizing, there was a 6.8% reduction (p = 0.001). A comparison of the groups showed no significant differences between them. Conclusions. The jumps after the two stretching routines were significantly lower. Submaximal or maximal (flexibilizing) stretching exercises reduced the explosive force of vertical jumps, although the differences between the training intensities were not significant.